Indian sugar policies: connecting production, consumption, and health - Shweta Saini; Pulkit Khatri; Siraj Hussain (Agricultural Economics Research Review, 2023)
Sugar is one of the most regulated agricultural commodities in India. Every stage of its value addition has some mechanism of government support. Sugar emerges to be an interesting case study which shows how one market distortion triggers a spate of distortionary policies resulting in a highly distorted domestic sugar market, which at many times stands alienated from its global reference prices. The observed and estimated costs (actual and implied) of policy interventions by the government in the cane and sugar industry are high and have been rising overtime. Combining them with the high environmental and social costs, there emerges a need for a course correction in policies.